2008
DOI: 10.4102/sajip.v34i1.415
|View full text |Cite
|
Sign up to set email alerts
|

Perception of organisational commitment, job satisfaction and turnover intentions in a post-merger South African tertiary institution

Abstract: A merger can be considered both a phenomenological and signifcant life event for an organisation and its employees, and how people cope with and respond to a merger has a direct impact on the institutional performance in the short to medium term. It is within this context that post-merger perceptions of a tertiary institution were investigated. A predictive model (determined the “best” of 15 predefned models) of turnover intentions was developed for employees of a South African tertiary institution (having und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
110
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(133 citation statements)
references
References 55 publications
13
110
1
9
Order By: Relevance
“…On the other hand, older workers were affectively more committed to their organisations seemingly due to the perceived costs of leaving their organisations and having 'cognitively justified' their continuance in an organisation. Several studies have reported a trend whereby older employees tend to report greater organisational commitment (Martin & Roodt, 2007). The findings are consistent with those of Levy (2010) andD'Manto andHerzfeldt (2008), who found older employees to be more committed.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, older workers were affectively more committed to their organisations seemingly due to the perceived costs of leaving their organisations and having 'cognitively justified' their continuance in an organisation. Several studies have reported a trend whereby older employees tend to report greater organisational commitment (Martin & Roodt, 2007). The findings are consistent with those of Levy (2010) andD'Manto andHerzfeldt (2008), who found older employees to be more committed.…”
Section: Discussionsupporting
confidence: 81%
“…Employment equity legislation has enhanced career mobility for historically disadvantaged groups. Various studies have explored the relationship between external career mobility and, more specifically, intent to leave and race (Martin & Roodt, 2007;Vallabh & Donald, 2001). White South African employees experienced greater levels of satisfaction for several job facets, including promotional opportunities, which is a key aspect of perceived intraorganisational career mobility (Lumley, 2009).…”
Section: The South African Contextmentioning
confidence: 99%
“…The importance of organizational commitment has been emphasized in the literature as it relates to many subjects (i.e., job, profession, career, business) in many areas (i.e., sociology, industrial psychology, health psychology) (Martin and Roodt, 2008). Although much research has been done, often using improper scales, organizational commitment can be difficult to synthesize and define (Meyer and Allen, 1991;Kimbel, 2002).…”
Section: Organizational Commitmentmentioning
confidence: 99%
“…Numerous studies on commitment have been undertaken in the disciplines of behavioural, attitudinal and motivational sciences, within three broad research streams, through sociological, industrial and organisational psychology and health psychology [9]; all emphasise the importance of commitment in the workplace. It has been the subject of excessive research and empirical attention, as a consequence and an antecedent of other workrelated variables [8] and has been linked to workplace outcomes [10].…”
Section: Vocational Teacher Working Commitmentmentioning
confidence: 99%
“…Commitment in the workplace has evolved to encompass a broad range of types, such as engagement, attachment, commitment and involvement [8]. Numerous studies on commitment have been undertaken in the disciplines of behavioural, attitudinal and motivational sciences, within three broad research streams, through sociological, industrial and organisational psychology and health psychology [9]; all emphasise the importance of commitment in the workplace.…”
Section: Vocational Teacher Working Commitmentmentioning
confidence: 99%